Epigeic invertebrates of pig‐damaged, exposed wetland sediments are rooted: An ecological response to feral pigs (Sus scrofa). Issue 12 (12th October 2020) - Marshall, Jonathan C.; Blessing, Joanna J.; Clifford, Sara E.; Negus, Peter M.; Steward, Alisha L.
Abstract: 1. Feral pigs ( Sus scrofa ) are widespread and cause significant damage to the ecological and cultural values of wetlands through their rooting, pugging, and wallowing behaviour. 2. The impacts of feral pigs on the epigeic (ground surface) invertebrates of exposed wetland sediments were investigated using 48 composite pitfall samples collected from 21 sites over three occasions in the Archer River catchment, north Queensland, Australia. Feral pig damage was quantified in transects along the margins of the wetlands. We tested the prediction that invertebrate assemblages would demonstrate reduced taxon richness and abundance, and altered assemblage composition, with an increasing intensity of pig damage. 3. Pig damage to exposed wetland sediments was a stressor to epigeic invertebrates in this environment, where there was a diverse invertebrate fauna. As expected, both taxon richness and abundance were significantly limited by pig damage, as was variability in multivariate assemblage composition. Thirty‐one epigeic invertebrate taxa (66%) showed a decrease in their frequency of occurrence, mean abundance, or both, at sites with high levels of pig damage, relative to sites with low levels of pig damage. Certain families of spiders, beetles, snails, and freshwater crabs were among the taxa more prevalent when pig damage was low, whereas none of those taxa was more prevalent when pig damage was high. 4. There are biodiversity conservation ramifications from these results as pigs threaten elements of this fauna and thus wetland biodiversity, but the taxonomy, ecology, and distributions of epigeic invertebrates of exposed wetland sediments are poorly known. 5. The intensity of pig damage and the richness and abundance of epigeic invertebrates, as measured here, provide useful monitoring indicators to evaluate the effectiveness of pig control measures wherever pigs damage wetlands.